The Problem of Periodization of South Slavic Literatures, 24-26 April, 1987. University of Michigan, Ann Arbor - Gjurgjan, Ljiljana Ina (1987)
The paper has addressed the problem of the atypical literary history regarding the canonized periodization of history of literature. It has argued against the colonizing view that such a literature is irregular (and thus inferior(. Instead, it has advocated the critical approach that would see each national literature as one of the cultural products in its own right, not more or less valuable because it more or less replicates the canonized literary history.